ANALISA RASIO KEUANGAN TERHADAP RETURN ON ASSET PADA SUBSEKTOR BANK YANG TERDAFTAR DI BEI - Lumbangaol, Frima; Trinanda, Windi Astria; Aprilia, Putri; Simanjuntak, Ckristina Meilinda (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2019)
This study aims to examine the Capital Adequacy Ratio (CAR), BOPO and Loan to Deposit Ratio (LDR) partially and simultaneously to Return On Assets (ROA) in banking companies listed on the Indonesia Stock Exchange for the 2012-2017 period. The research sample was obtained by 28 selected companies using purposive sampling with certain criteria. The type of data used in this study is quantitative data. The data source in this study is secondary data. Data collection techniques in this study are multiple analysis models (linear), classic assumption tests and hypothesis testing in analyzing research data. the results of the research partially show that the Capital Adequacy Ratio (CAR) and Loan to Deposit Ratio (LDR) have a positive and significant effect while the BOPO has a negative but not significant effect on Return On Assets (ROA) on banking companies listed on the Indonesia Stock Exchange. Simultaneously the Capital Adequacy Ratio (CAR), BOPO and Loan to Deposit Ratio (LDR) have a significant effect on Return On Assets (ROA) in banking companies listed on the Indonesia Stock Exchange.